Keterkaitan Opini Wajar Tanpa Pengecualian Dari Badan Pemeriksa Keuangan Terhadap Prinsip Good Financial Governance - Brillian Willis; Lanny Kusumawati; Wafia Silvi Dhesinta Rini (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study is to examine the relationship between the implementation of good financial government with unqualified opinion. The type of research method used in this study is a normative juridical method by conducting a literature study on related legal materials. The results of this study are that there is a relationship between Unqualified Opinion issued by the Supreme Audit Agency and the principle of good financial government, one of the benchmarks of which is based on Government Accounting Standards regulated in Article 32 of Law Number 17 of 2003 concerning State Finance in order to present the results of the technical performance of the State Audit Board of the Republic of Indonesia on the examination of financial statements in accordance with the standards and laws and regulations. Unqualified Opinion is a manifestation of the values of good governance, namely accountability, participation, and transparency, but this does not rule out the possibility that there are irregularities that cannot be detected during the audit process and do not guarantee the absence of corruption by government administrators. Keywords: Supreme Audit Agency; Unqualified Opinion; Good Financial Government.